In vitro evaluation of antimicrobial efficacy of silver zeolite against common oral pathogens - Sangram Panda; Shakti Rath; Mirna Garhanayak; Sourav Chandra Bidyasagar Bal; Ramesh Nagarajappa (National Institute of Public Health - National Institute of Hygiene, 2021)
Objectives. Antimicrobial efficacy and toxicity analysis of 5 different concentrations of silver zeolite (SZ) compound against 5 common oral pathogens Streptococcus mutans, Streptococcus pyogenes, Lactobacillus sp., Staphylococcus aureus, Candida albicans. Material and methods. The antimicrobial efficacy of 5 different concentrations of SZ was tested against 5 common oral pathogens using the agar well diffusion method and the MIC and MBC values were determined using the micro broth dilution method. The toxicity of all 5 different concentrations was evaluated using brine shrimp assay and lethal concentration (Lc50) value was determined. Results. At 10 μg/mL the antimicrobial activity of SZ was almost negligible. The antimicrobial activity was observed in an increasing trend against all the test microorganisms as the concentration increased. At 75 & 100 μg/mL the zone of inhibitions was more than the control. Furthermore, MIC and MBC values of SZ with concentrations 25, 50, 75, and 100 μg/mL were determined and recorded. SZ was equally effective against all the test organisms. The LC25 (lethal concentration25) value was 1.6 μg/mL, whereas the LC50 value was 1.77 μg/mL and the LC75 value was 1.90 μg/mL, calculated from the probit computational method. Conclusion. SZ has the potential to change the ongoing system and bring about a revolution as an antimicrobial drug. However, the dose must be regulated as it can be toxic in higher concentrations. SZ compounds with the correct study of physicochemical properties and toxicity analysis can increase their pharmacological use and market value.